Sweet scarf - Mohamad, Siti Nur Afiqah; Ahmad Fadzil, Shawn Rizal; Abdul Rani, Nur Ayu Hazira; Rustam, Nurul Qistina; Ismail, Nur’aina ‘Aqilah (2020)
Sweet Scarf is a new online business, selling as well as providing women and ladies from different age groups, the best kind of material shawls to wear. Although simple, the product is yet elegant and eye-catching. Sweet Scarf puts modesty first above all. This business consists of five (5) young individuals whose mission is to build and grow Sweet Scarf into being the people’s favourite online scarves (shawl) store. As the leader of the group, the General Manager, Nur Ayu Hazira makes sure that every product sold is good in quality and loved by the buyers. Products offered by Sweet Scarf include a scarf collection of a snowcap (anak tudung) along with a built-in mask scarf, a selection of scarfs for younger ages and a selection of instant-wear shawls. The marketing plan aims to provide an effective promotional strategy across four different customer segmentations, namely the young adults (students), families, senior citizens and middle-to-upper income class segments. As for operational plan, it will focus on the systematic and effective system in production of our products in order to reach the objectives. Furthermore, the profitability in the financial plan, the net profit of this business increases for each year. This is due to its increasing recognition from another people other than the usual customers. In the first year, the net profit of Sweet Scarf is RM 8,940 meanwhile as for the second and third year, the net profit for each is RM 11,993 and RM 27,095 respectively.